c.1 - Belshaw, Horace (New York, 1956)
The scope of this essay is restricted to a consideration of the relationship between population growth and levels of consump tion in so-called 'under-developed' countries in Asia. I shall regard economic development as a social process which results in a cumulative increase in levels of consumption. The selection of Asian countries for consideration is determined partly by the fact that I have had more opportunities for personal observations in Asia than in other under-developed areas, and am more familiar with the literature dealing with this region than with others, so that more information about Asian countries is at present avail able to me; partly because many of them illustrate rather clearly the nature of population problems. Of course, conditions differ from country to country, but to consider each country separately would require an encyclopædia volume and more detailed infor mation than is available from most of them. But conceptually or analytically the problems are similar in all, and with the usual reservations as to the necessity for taking account of national differences in approaching the applied problems, it seems possible to formulate generalizations which provide a framework within which these problems can be considered in all of them.
Keywords: Population